Effect of Ornamental Celery Leaves on Blood Pressure in Hypertension Patients - Bella Juwita; Juli Andri; Andry Sartika; Padila Padila; Muhammad Bagus Andrianto (Jurnal Keperawatan Silampari, 2026)
This study aimed to determine the effect of celery on reducing hypertension in patients at the Kandang Community Health Center in Bengkulu City. This quantitative study employed a quasi-experimental pre-test and post-test design. The statistical analysis of celery leaf decoction showed a p-value ≤ 0.005, thus Ha was accepted and Ho was rejected. In conclusion, there was an effect on hypertension after administering celery leaf decoction to hypertensive patients at the Kandang Community Health Center in Bengkulu City.   Keywords: Hypertension, Celery, Blood Pressure